Religions of Rome : volume 1 - A History - Beard, Mary, 1955-; North, John, 1938-; Price, S. R. F (Cambridge ; New York : Cambridge University Press, 1998)
Volume - reveals the extraordinary diversity of ancient Roman religion. A comprehensive sourcebook, it presents a wide range of documents illustrating religious life in the Roman world - from the foundations of the city in the eighth century BC to the Christian capital more than a thousand years later. Each document is given a full introduction, explanatory notes and bibliography, and acts as a starting point for further discussion. Through paintings, sculptures, coins and inscriptions, as well as literary texts in translation, the book explores the major themes and problems of Roman religion, such as sacrifice, the religious calendar, divination, ritual, and priesthood. Starting from the archaeological traces of the earliest cults of the city, it finishes with a series of texts in which Roman authors themselves reflect on the nature of their own religion, its history, even its funny side. Judaism and Christianity are given full coverage, as important elements in the religious world of the Roman empire
Volume I: History : -- Early Rome --- 2. imperial triumph and religious change --- 3. Religion in the late Republic --- 4. The place of religion: Rome in the early Empire --- 5. The boundaries of Roman religion --- 6. The religions of imperial Rome --- 7. Roman religion and Roman Empire -- 8. Roman religion and Christian emperors: fourth and fifth centuries ------ Volume II: A sourcebook : -- 1. Earliest Rome --- 2. The deities of Rome --- 3. The calendar --- 4. Religious places --- 5. Festivals and ceremonies --- 6. Sacrifices --- 7. Divination and diviners --- 8. Priests and priestesses --- 9. Individuals and gods: life and death --- 10. Rome outside Rome --- 11. Threats to the Roman order --- 12. Religious groups --- 13. Perspectives
Includes glossary
Includes bibliographical references and index
Keywords: Rome -- Religion; Europe -- Religion -- History